The bookseller of Kabul - Seierstad, Asne. (b, 2003)
Capturing the harsh realities of life in modern-day Afghanistan and the plight of Afghan women, the Norwegian journalist provides a portrait of a committed Muslim man, a bookseller, and his family living in post-Taliban Kabul, Afghanistan. Reading Group Guide included
Keywords: Booksellers and bookselling -- Afghanistan -- Kabul